Enhancing The Excellence of Quality Management System Auditors: A Competency-Based Training Model with Instructional Design Strategic Approaches and Measurable Outcomes - Surono, Surono (Green Publisher Indonesia, 2024)
The development and implementation of a competency-based training model for Quality Management System (QMS) auditors are crucial for enhancing audit quality and organizational performance. This study identifies and addresses gaps in current auditor training programs through a structured approach that includes clear instructional goals, effective assessment tools, and robust instructional strategies. The research utilizes Training Needs Analysis (TNA) data and aligns training objectives with industry expectations through Occupational Standards and Competency Standards. Learning outcomes are formulated using the ABCD method (Audience, Behaviour, Condition, Degree) to ensure clarity, measurability, and achievability. The training program employs Outcome-Based Learning and Teaching (OBLT) methodologies, ensuring that the focus remains on achieving specific competencies. Self-assessment based on competency standards encourages reflective learning and self-improvement, while competency-based assessments measure the effectiveness of the training and the skills acquired by participants. The program culminates in the awarding of Micro Credentials and Certificates of Competency, which are traceable to national and international standards, thereby validating the skills and knowledge gained. Through rigorous testing and evaluation involving experts, educators, and participants, the study refines the training model to ensure its effectiveness and relevance. The findings indicate that the competency-based training model significantly improves the skills and performance of QMS auditors, leading to more effective audits and continuous quality improvement within organizations. This research contributes to the field by providing a comprehensive, evidence-based approach to developing high-quality training programs for QMS auditors.